Field irrigation using magnetized brackish water affects the growth and water consumption of Haloxylon ammodendron seedlings in an arid area - Guo, Yi; Wang, Quanjiu; Zhao, Xue; Li, Zongyu; Li, Mingjiang; Zhang, Jihong; Wei, Kai (Frontiers in Plant Science, 2022)
Freshwater resources in arid areas are scarce, while there are abundant brackish water reserves that have great application potential for the irrigation of desert plants. However, brackish water irrigation will lead to soil salinization, which will inhibit plant growth. Magnetized water is a new technology that makes the use of brackish water feasible. The present study assessed the effects of irrigation using three water types (fresh, brackish, and magnetized brackish water) and five irrigation amounts (W1, 81 mm; W2, 108 mm; W3, 135 mm; W4, 162mm; and W5, 189 mm) on soil salinity and Haloxylon ammodendron seedling growth. Compared with fresh water, brackish water irrigation inhibited the growth of H. ammodendron and reduced the water consumption. Irrigation with magnetized brackish water effectively improved the effect of soil salt leaching, promoted the growth and water absorption of H. ammodendron roots, and stimulated the growth of plant height, basal diameter, shoot length, and crown width. Based on principal component analysis, the first three treatments of H. ammodendron comprehensive growth state were FW4, FW3 and MBW4, respectively. This showed that magnetized brackish water combined with appropriate irrigation amount was helpful to optimize the growth of H. ammodendron seedlings on the basis of fresh water saving. Therefore, magnetized brackish water irrigation is an effective strategy for ensuring the establishment and growth of H. ammodendron seedlings in arid and water deficient areas.